Vocational Education and Training Policy between Indonesia and Tanzania - Mursyid, Andi Miftahul Maulidil; Zulihi, Zulihi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This article is a non-research-based article discussing vocational education and training (VET) between Indonesia and Training. The purpose of this article is to give comprehensive knowledge regarding the policy practices to the field of educational sectors particularly in vocational education and training between two countries (Indonesia and Tanzania). To begin, the writers give an overview regarding the VET policy between Indonesia and Tanzania. Both countries have in common when it comes to the objectives of VET programs. Furthermore, the writers discuss about the policy drivers which they view that the VET policy is driven by the demand of industrial sectors. Moreover, comparing and analyzing policy document between Indonesian and Tanzanian VET policy practice which are found that both countries have significant discrepancy in terms of the organizer of VET. Also, both countries face several challenges to implement VET program according to the result of STEEP analysis.